2000
DOI: 10.1016/s1074-7613(00)80218-6
|View full text |Cite
|
Sign up to set email alerts
|

CD4 + T Cell–Mediated Tumor Rejection Involves Inhibition of Angiogenesis that Is Dependent on IFNγ Receptor Expression by Nonhematopoietic Cells

Abstract: Immunity against MHC class II tumors can be mediated by CD4+ T cells in the effector phase through an unknown mechanism. We show that this is IFN gamma dependent but does not require IFN gamma receptor (IFN gamma R) expression on tumor cells, T cells, or other hematopoietic cells and that IFN gamma R expression is not necessary in the priming phase. However, tumor immunity requires IFN gamma R expression on nonhematopoietic cells in the effector phase and involves inhibition of tumor-induced angiogenesis. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
385
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 462 publications
(415 citation statements)
references
References 42 publications
27
385
0
3
Order By: Relevance
“…The acquired immunity against IFN-g-transfected RT2 glioma cells was postulated to be primarily caused by the antiangiogenic activity of the secreted cytokine (Fathallah-Shaykh et al, 1998). Qin and Blankenstein (2000) and Qin et al (2003) showed that rejection of different tumours by CD8 þ T cells was always preceded by inhibition of tumour-induced angiogenesis. Moreover, in some murine models, the antiangiogenic activity mediated by IL-12 and IL-18 was shown to be IFN-g mediated (Voest et al, 1995;Cao et al, 1999), and inhibition of angiogenesis by IFN-g was found to occur in colon carcinoma through transcriptional silencing of perlecan gene expression (Sharma and Iozzo, 1998).…”
Section: Inhibition Of Cam Vascularisation By Sponges Treated With Acmentioning
confidence: 99%
See 1 more Smart Citation
“…The acquired immunity against IFN-g-transfected RT2 glioma cells was postulated to be primarily caused by the antiangiogenic activity of the secreted cytokine (Fathallah-Shaykh et al, 1998). Qin and Blankenstein (2000) and Qin et al (2003) showed that rejection of different tumours by CD8 þ T cells was always preceded by inhibition of tumour-induced angiogenesis. Moreover, in some murine models, the antiangiogenic activity mediated by IL-12 and IL-18 was shown to be IFN-g mediated (Voest et al, 1995;Cao et al, 1999), and inhibition of angiogenesis by IFN-g was found to occur in colon carcinoma through transcriptional silencing of perlecan gene expression (Sharma and Iozzo, 1998).…”
Section: Inhibition Of Cam Vascularisation By Sponges Treated With Acmentioning
confidence: 99%
“…Antiangiogenic effects of IFN-g, in fact, have been described in humans as well as in several in vitro and in vivo models. Precisely, murine IFN-g produced by either CD4 þ or CD8 þ cells inhibits tumour-induced angiogenesis in syngeneic tumour models (Saiki et al, 1992;Qin and Blankenstein, 2000;Blankenstein and Qin, 2003). Human IFN-g inhibits proliferation and migration of human endothelial cells and capillary tube formation in vitro (BroutyBoye and Zetter, 1980;Friesel et al, 1987;Tsuruoka et al, 1988;Maheshwari et al, 1991;Albini et al, 2000) and represses lymphocyte-induced tumour angiogenesis (Sidky and Borden, 1987).…”
mentioning
confidence: 99%
“…In spite of the recognized importance of Ag-specific CD4 1 T cells in both adaptive and innate immune responses, their identification remains elusive, and their in vitro amplification is hindered by the absence of reliable protocols able to support cell proliferation in the absence of terminal differentiation. While, Ag tumours elicit natural tumour-specific CD4 1 T-cell responses [4][5][6][7][8][9][10], functional tolerance is eventually observed through the induction of T-cell anergy [11,12], T-cell depletion [13] or the limitation of the memory repertoire [10,14,15]. This is possibly due to Ag persistence, and continual TCR signaling, as in the case of chronic viral infections [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Essentially, CD4 þ T cells recognise peptides presented on MHC class II molecules expressed primarily on antigen-presenting cells. Although most tumour cells do not express MHC class II molecules, CD4 þ T cells can effect an antitumour response in the absence of CD8 þ T cells by secreting cytokines, such as interferon-g (Mumberg et al, 1999;Qin and Blankenstein, 2000), or by activation and recruitment of effector cells such as macrophages and eosinophils (Greenberg, 1991;Hung et al, 1998). However, the main role of CD4 þ T cells in the immune response to cancer is to prime CD8 þ cells and maintain their proliferation.…”
mentioning
confidence: 99%